Slow pathway modulation in a patient with tricuspid valve atresia. (21st November 2013) - Frommeyer, Gerrit; Milberg, Peter; Eckardt, Lars; Mönnig, Gerold
Abstract Owing to increased life expectancy, patients with grown-up congenital heart disease nowadays present various types of arrhythmias. We report treatment of a 27-year-old patient with tricuspid and pulmonary atresia who was referred to our department with symptomatic tachycardia. During electrophysiologic study, a diagnosis of typical AV-nodal re-entrant tachycardia was made, and he was successfully treated despite the described anatomic malformation.